Revitalization of the Mgmp Program to Improve the Pedagogic Competence of High School Science Teachers (SMA) - Munajat, Salim; Wasliman, Iim; Suhendraya Muchtar, Hendi; Iriantara, Yosal (CV. Inara, 2022)
The Subject Teacher Conference (MGMP) as an association or association of teachers plays a strategic role in improving and strengthening teacher competence through discussion and training. Its main role is to facilitate teachers in the same field of study in exchanging opinions and experiences. However, there are still many teachers who are not active so that they do not develop and are static even though they have participated in MGMP activities. In addition, due to the limited number of roles that can be performed by the MGMP, the ability of teachers to teach as indicated by the indicators of student success is still low. The purpose of this study was to find out how